Relationship between pulmonary function and brachial-ankle pulse wave velocity in coal miners in northern China - Yan, Xinhua; Sun, Lixia; Ma, Mengying; Liu, Jiqiang; Wu, Shouling; Cao, Jie (Journal of thoracic disease, 2019)
To investigate the relationship between pulmonary function and brachial-ankle pulse wave velocity (baPWV). A cross-sectional study was conducted. A total of 11,388 people with complete pulmonary function test and baPWV data and who participated in both the health examination of the Kailuan Occupational Disease Prevention and Treatment Center in 2014-2016 and the health checkup of the Kailuan Group in 2012 and 2014 were selected as subjects. The study population was divided into four groups by forced vital capacity (FVC) quartiles (group 1: FVC <3.50 L; group 2: 3.50 L ≤ FVC <3.96 L; group 3: 3.96 L ≤ FVC <4.47 L; group 4: FVC ≥4.47 L) and divided into four groups by forced expiratory volume in one second (FEV1) quartile (group 1: FEV1 <3.15 L; group 2: 3.15 L ≤ FVC <3.61 L; group 3: 3.61 L ≤ FVC <4.08 L; group 4: FVC ≥4.08 L). Linear regression analysis and multivariate logistic regression were used to analyze the effects of pulmonary function on baPWV. When grouped by FVC, the baPWV of the first group was significantly higher than the other groups. Similarly, the incidence of arteriosclerosis in the first group was significantly higher than the other groups. When grouped by FEV1, the baPWV of the first group was significantly higher than the other groups. The incidence of arteriosclerosis was also significantly higher in the first group than the other groups. After correcting for other confounding factors using linear regression, it was found that the effects of FVC and FEV1 on the study subject's baPWV were -23.84 and -24.65 L, respectively. Multivariate logistic regression analysis showed that when grouped by FVC quartile, the risk of arteriosclerosis was increased by 34% in group 1 compared with group 4 (OR: 1.34, 95% CI: 1.17-1.52); the risk of arteriosclerosis was increased by 16% in group 2 compared with group 4 (OR: 1.16, 95% CI: 1.03-1.31). When grouped by the FEV1 quartile, the risk of arteriosclerosis was increased by 25% in group 1 compared with group 4 (OR: 1.25, 95% CI: 1.10-1.42). Decreased pulmonary function is negatively correlated with baPWV and is an independent risk factor for arteriosclerosis.